High stakes : Florida Seminole gaming and sovereignty - Cattelino, Jessica R. (Duke University Press, 2008)
Ethnography that looks at how the casinos run by the Florida Seminoles have affected the tribe's ideas about sovereignty and cultural distinctiveness.